Nutrient enrichment alters phytoplankton biomass and composition via silicon limitation - Makareviciute-Fichtner, Kriste; Matthiessen, Birte; Lotze, Heike K.; Sommer, Ulrich (Frontiers in Marine Science, 2024)
Despite management efforts, anthropogenic nutrient enrichments continue to enhance phytoplankton blooms worldwide. Release of nitrogen and phosphorus compounds not only provides surplus of nutrients but also disbalances their stoichiometry. Declines in the relative availability of dissolved silicon might induce limitation in diatoms, major primary producers with silicified shells. We studied experimentally how nutrient enrichment and resulting decline in dissolved silicon to nitrogen ratios (Si:N) affect the structure and functioning of natural plankton communities. Nitrate was added to create a range of Si:N ratios and phosphate was supplied in Redfield ratio to nitrogen. We also manipulated copepod abundance to understand the top-down effects on communities experiencing nutrient enrichment. Nitrogen and phosphorus additions resulted in a steep phytoplankton biomass increase, followed by a post-bloom decline. Phytoplankton bloom biomass was higher in high nitrogen treatments but during the post-bloom period this trend switched. Biomass was sustained longer in high Si:N treatments, indicating that silicon limitation terminates the bloom. Many diatom species did not benefit from nitrogen and phosphorus enrichment and diatom dominance ceased below Si:N of 0.4:1. Under high grazing pressure, silicate was taken up faster suggesting that silicification is important in diatom defense. Copepods shaped plankton communities via feeding on dinoflagellates, chlorophytes and the diatom Skeletonema costatum but there was no significant effect of nitrogen and phosphorus enrichment on copepod abundance. Our results, combined with previous studies, show that while nutrient concentrations define the total phytoplankton bloom biomass, resource ratios are important in sustaining biomass and determining community structure and composition.